CORRELATION BETWEEN PREOPERATIVE OPHTHALMOLOGIC EXAMINATION AND POSTOPERATIVE VISUAL FUNCTION IN PATIENTS WITH PITUITARY ADENOMA: A RETROSPECTIVE STUDY - Rahma Putri, Herdanti; Nusanti, Syntia; Ananda Aman, Renindra; M, Sidik; Dewiputri, Salmarezka; Paramita Ayuningtyas, Sita (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Pituitary adenoma is a benign tumor of the pituitary gland that can be treated surgically. Ophthalmological examination is a standard protocol to determine surgical indications and assess postoperative visual prognosis. Objective: This study aimed to evaluate postoperative visual function in pituitary adenoma patients and compare it with preoperative findings. Methods: Retrospective study using medical record data of all pituitary adenoma patients who underwent tumor removal surgery and neuro-ophthalmological examination at Cipto Mangunkusumo Hospital from 2019-2021 . Results: 63 pituitary adenoma patients were included in the study. Median best-corrected visual acuity (BCVA) at the last follow-up improved from 0.8 to 0.45 logMAR in the new case group and from 0.45 to 0.15 logMAR in the residual case group. The most common visual field defect in this study was temporal hemianopia with significant difference in mean deviation (MD) and visual field index (VFI) after surgery on both groups (p<0,05). Moreover, the correlation between initial and final VA, MD, and VFI was significant (0,781; 0,701; 0,594, respectively). The remaining tumor volume was also a significant factor in the improvement of MD and VFI, with better MD and VFI values shown in a smaller tumor volume postoperatively. Conclusion: Neuro-ophthalmological examination after surgery showed an increase in BCVA and improvement in visual field defects. It is shown to be correlated with preoperative BCVA, preoperative MD, and VFI on Humphrey Visual Field examination, and postoperative tumor volume.